Growth, Phenology and Yield Attributes of A White Maize Genotype Sauwmopmdt273 Under Different Planting Configurations (Bangladesh Agronomy Journal, 2024)
A field experiment was carried out at the agronomy field of Sher-e-Bangla Agricultural University, during the period from July to October, 2018 with fifteen planting configurations viz., T1 (40 cm × 15 cm), T2 (40 cm × 20 cm), T3 (40 cm × 25 cm), T4 (45 cm × 15 cm), T5 (45 cm × 20 cm), T6 (45 cm × 25 cm), T7 (50 cm × 15 cm), T8 (50 cm × 20 cm), T9 (50 cm × 25 cm), T10 (55 cm × 15 cm), T11 (55 cm × 20 cm), T12 (55 cm × 25 cm), T13 (60 cm × 15 cm), T14 (60 cm × 20 cm), and T15 (60 cm × 25 cm) to study the growth, phenology, yield attributes and yield of a white maize genotype SAUWMOPMDT273. The experiment was laid out in a randomized complete block design with three replications. Regarding growth and yield parameters, the treatment 60 cm × 25 cm showed significantly the maximum plant height, tassel length and leaf area at silking, grain filling and at harvest. The highest area of an individual leaf 477.9, 879.3, and 496.3 cm2 as well as stem dry matter weight of 28.73, 21.35, and 27.40 g plant-1 respectively, below cob-node, at cob-node and above the cob-node during silking obtained from treatment 60 cm × 25 cm. The treatment 55 cm × 25 cm showed maximum biological yield (14.64 t ha−1) and 60 cm × 20 cm showed significantly the highest cob length (15.94 cm) and number of grains row−1 (20.00), but the highest number of grains cob−1 (231.50), 100 seed weight (29.99 g), grain weight cob−1 (59.81 g) were recorded from 55 cm × 25 cm. Sparser configuration (60×20 cm) requiring less seed rate, this configuration may be followed.Bangladesh Agron. J. 2024, 26(2): 67-76